The PERAN TEKNOLOGI DALAM INOVASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Rina Diniati; Mukhlas, Mukhlas (Widya Balina, 2025)
The development of information and communication technology in the 21st century has driven a major transformation in the world of education, including in Islamic Religious Education (PAI). The learning process is no longer limited to conventional classrooms but has shifted to interactive and dynamic digital spaces. This study aims to analyze the role of technology in PAI learning innovation by reviewing its effectiveness, challenges, and implementation strategies from a pedagogical and theological perspective. Through a library research approach with content analysis of scientific literature, this study found that the use of digital technologies such as e-learning platforms, social media, and Islamic applications has the potential to strengthen the internalization of Islamic values ​​in a contextual and engaging manner for the digital native generation. However, the application of technology in PAI still faces various obstacles, such as disparities in access, low teacher digital literacy, and the threat of religious disinformation in cyberspace. Therefore, technology integration must be accompanied by strengthening digital ethics and the principles of maqāṣid al-syarī'ah to prevent the erosion of the spiritual value of Islamic education. The study's findings demonstrate that effective Islamic Religious Education (PAI) learning innovations focus not only on the use of digital media but also on character development and noble morals through holistic, creative, and humanistic learning designs. This research contributes to the formulation of a new paradigm for Islamic education that integrates technology and spirituality as a means of developing a generation of Muslims who are morally upright, critical, and adaptable to the challenges of the digital era.